(untitled) (Physical Education, Health and Social Sciences, 2025)
Introduction: Breast cancer and reconstructive surgery of the breast represent a multidisciplinary patient-centered treatment area with a need for efforts from different caregivers to provide the best possible care. (Multidisciplinary teams, MDTs) have led to dramatic improvements in the management of the patient as a whole and planning of breast surgery constituents as well as outcome in the long term. Objective: This paper aimed to re-visit the role of MDT in optimizing breast surgery, and how multidisciplinary within specialist units adds to better surgical accuracy, improved patient satisfaction and faster recovery post-operatively. Methods: Methods: A systematic review of the literature, including studies on MDTs in breast surgery, was conducted. PubMed, Scopus and Google Scholar databases were searched for studies between 2010 to March-2023. We also comprised articles in which there was a multidisciplinary collaboration or breast surgery outcomes. Evidence was summarized in relation to domains of influence: decision making around surgery including pre-operative planning, intra-operative and post-operative care, and patient satisfaction. Results: The findings demonstrated that MDTs had an important influence on surgical outcomes of breast surgery, particularly in the accuracy of surgical strategy planning, personalized treatment programs and reduction of complication rate. The oncologists and the radiologists collaborated to establish reliable localization of the tumor, while collaboration with plastic surgeons was a key factor for achieving better cosmetic as well as reconstructive outcomes. Satisfaction was more pronounced in subjects cared after MDTs and both psychopathological stress and definite relapses were significantly lower than in patients followed by single specialists only. Conclusions: Anesthetists, surgeons and radiologists need to work together in order to achieve the best results of a breast operation. This multidisciplinary holistic approach of MDTs confirmed in better preparation for and performance of surgery as well as less postoperative complications and higher patient’s satisfaction. This review outlines the requirement of MDT involvement in breast surgery and shows that more interdisciplinary work is required to outcome COC.